2023
DOI: 10.1097/upj.0000000000000394
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Billing and Reimbursement for Urology Office Visits Before and After Medicare Payment Reforms

Abstract: Introduction:The impact of Medicare reimbursement changes on urology office visit reimbursements has not been fully examined. This study aims to analyze the impact of urology office visit Medicare reimbursements from 2010 to 2021, with a focus on 2021 Medicare payment reforms.Methods:The Centers for Medicare and Medicaid Services Physician/Procedure Summary data from 2010-2021 were utilized to examine office visit CPT (Current Procedural Terminology) new patient visit codes 99201-99205 and established patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Lee and colleagues have nicely summarized the shift in reimbursement trends for a slew of common procedures done by urologists, urologic advanced practice providers (APPs), and interventional radiologists (IR). 1 While many procedures have been performed by the same providers for years, such as antegrade stent placement by IR and prostate biopsies by radiologists, the largest shifts are suprapubic tube (SPT) placement, SPT change, and renal ablation.…”
mentioning
confidence: 99%
“…Lee and colleagues have nicely summarized the shift in reimbursement trends for a slew of common procedures done by urologists, urologic advanced practice providers (APPs), and interventional radiologists (IR). 1 While many procedures have been performed by the same providers for years, such as antegrade stent placement by IR and prostate biopsies by radiologists, the largest shifts are suprapubic tube (SPT) placement, SPT change, and renal ablation.…”
mentioning
confidence: 99%
“…Dr Lee and colleagues examined the changes in urology office visit reimbursement before and after the 2021 Medicare Payment Reform, a reform aimed at reducing documentation, simplifying CPT coding, and using time as a dominant metric for determining billing code. 2 This coding reform was hypothesized to increase reimbursements for urology office visits, although prior studies revealed decreased reimbursement across urological procedures over time. 3…”
mentioning
confidence: 99%